Staphyphage: Biorisk Reduction in MRSA Research - Tan, Cheng Siang; Nurul Aqilah, Binti Aqiludeen; Gowbei, Annabel; Mijen Beemer, Alexander; Santhana, Raj L.; SIti Fairouz, Binti Ibrahim (2017)
Staphylococcus aureus is an opportunistic human pathogen that has the ability to cause both health care-associated and community-acquired infections [1]. It has been identified as one of the ‘high priority pathogen’ by the World Health Organization (WHO) [5] The infections were once, easily treated with antibiotics before resistance against beta-lactams (eg. Methicillin) and glycopeptides (eg. Vancomycin) began to emerge over the years and caused an increase in mortality and morbidity rates in patients infected with S. aureus [2,3]. This has led to an increased interest in the exploration of the use of bacteriophage as an alternative approach way to combat MRSA because a bacteriophage has bacteriolytic mechanism independent from those of any known antibiotics [5]. The availability of a virulent and broad spectrum bacteriophage against MRSA may significantly reduce the overall biorisk as it acts as an effective treatment in case of exposure.